The Impact of Service Quality on Customer Satisfaction in Islamic Banking in Tanzania - Fatma Hemed Suleiman (Ekonomi Islam Indonesia, 2025)
The purpose of this study is to analyse the impact of the service given by an Islamic bank institution in Tanzania on customer satisfaction using the CARTER model, which identifies the major factors that influence consumer perception. Questionnaires are disseminated throughout Tanzania's many regions where Islamic banks operate, including Zanzibar, Dar es Salaam, Dodoma, and Arusha, using stratified random sampling. Data was analysed using the structural equation model (SEM) with SPSS and AMOS version 20 to determine the link between service quality and customer satisfaction. The study found that reliability, assurance, and compliance all have a highly favourable and significant impact on customer satisfaction, with reliability being the most significant and positively associated. On the other hand, empathy and tangibility have a negative link with customer satisfaction; notably, responsiveness has no impact on the customer satisfaction neither positive nor negative signification. That is, responsiveness alone may not have an impact on client satisfaction at Tanzanian Islamic banks. Tanzania Islamic Bank should encourage more enhancement of reliability, assurance, and compliance in their delivery of their services to their customers because doing that can bring trustworthy and accurate services that align with the Islamic rules and regulations that lead to strong loyalty and relationships.